MAKING A MORE HOSPITABLE PUBLIC NOTICE - Sukarsono, Sukarsono (Pusat Pengembangan Bahasa IAIN Tulungagung, 2015)
This article explores the nature of public notice in Indonesian community. My aim in the first place is to describe the nature of public notices as to explain why some of them sound inhospitable or even impolite. The very apparent factors are due to the presence of words that imply writer’s exercise of power and thus a subordination to the readers occurs. In addition, I also try to propose some pragmatics recomendations for the writer of public notice in order to compose an effective, yet still polite, public notice through the accounts of context and politeness theory.